An evaluation of a possible increase in self-knowledge through a career counselling intervention for grade 11 learners in previously disadvantaged schools - Du Toit, Annette (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCom)--Stellenbosch University, 2015.